Pengolahan Tulang Ikan Selengek Menjadi Kaldu Bubuk Sebagai Produk Pangan Berdaya Saing Kawasan Kota Tuo Bengkulu - Revi Yuliana; weny Listiana; Hadiwia Kusuma; Mujiono Mujiono; Diah Azhari (Universitas Dehasen Bengkulu, 2023)
Fish bone is a residual form of fish processing which has not been utilized much and has high potential to be developed as a value-added product. In the Tuo Bengkulu City area, fish are a source of income for the local community, but this potential has not been maximized due to a lack of knowledge and skills in processing fish bones. One of the types of fish in question is the selengek fish or also known as the selengek fish. The meat from the selengek fish can be used as a raw material for making dim sum, dumplings, nuggets and meatballs. Meanwhile, the bones can be processed into powdered broth or food seasoning ingredients. In order for meat and bones to be made into products that have added value, it is necessary to innovate and create products made from selengek fish. In addition, in order for the product to become a new business opportunity, it is necessary to carry out a business feasibility calculation that is used to measure the chances of success for a business in the future. We carried out the activity we meant with the management of the Kelompok Pemanfaatan dan Pemeliharaan (KPP) Kota Tuo.